1966
DOI: 10.1111/j.1550-7408.1966.tb01978.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracer Experiments in Feeding Littoral Foraminifera*†‡

Abstract: SYNOPSIS. Tracer technic has proved to be an excellent tool in the study of predator‐prey relationships among the foraminifera. More than fifty axenic species of protists including diatoms, dinoflagellates, chlorophytes, chrysophytes, cyanophytes, bacteria and yeasts were tested as potential food for Allogromia sp (NF), A. laticollaris, Am. monia beccarii, Quinqueloculina spp, Rosalina floridana, Anomalina sp, Elphidium sp, Spiroloculina hyalina, Globigerina bulloides, and Globorotalia truncatulinoides. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

1975
1975
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 19 publications
(8 reference statements)
2
55
0
2
Order By: Relevance
“…7). Lee et al (1966) observed that smaller (~150 to 200 µm) specimens of Allogromia laticollaris ingested more food than larger (350 to 400 µm) ones. Similar size-dependent ingestion of bacteria was observed for the same species, although the numbers of samples were limited (Langezaal et al 2005).…”
Section: Size-dependent Ingestion Of Chlorella Sp By Uvigerina Akitamentioning
confidence: 95%
See 1 more Smart Citation
“…7). Lee et al (1966) observed that smaller (~150 to 200 µm) specimens of Allogromia laticollaris ingested more food than larger (350 to 400 µm) ones. Similar size-dependent ingestion of bacteria was observed for the same species, although the numbers of samples were limited (Langezaal et al 2005).…”
Section: Size-dependent Ingestion Of Chlorella Sp By Uvigerina Akitamentioning
confidence: 95%
“…The in situ experiments were carried out for 9 d. The 9 d interval may be sufficient to induce indirect Some benthic foraminiferal species are known to utilize bacterial carbon under experimental conditions (Lee et al 1966, Bernhard & Bowser 1992, Langezaal et al 2005. However, the contributions of bacterial carbon to the total carbon requirements of foraminifera are generally low based on direct evaluation in labeling experiments (Nomaki et al 2006, van Oevelen et al 2006b, Pascal et al 2008.…”
Section: Via Microbial Processesmentioning
confidence: 99%
“…G. bulloides presents biological characteristics that place it on the border between spinose and non-spinose species; while most spinose species carry algal symbionts, G. bulloides does not (Gastrich, 1987;Hemleben et al, 1989;Schiebel et al, 1997). It is abundant in periods of high phytoplankton productivity (Prell and Curry, 1981;Reynolds and Thunell, 1985;Hemleben et al, 1989) and feeds on algal prey (Lee et al, 1966). G. bulloides is common in mid-latitude and subpolar waters, but it is also present in the subtropical waters of the Indian Ocean.…”
Section: Growth (Tg)mentioning
confidence: 99%
“…Foraminiferal populations have been shown to increase in response to blooms in primary production (Lee et al 1966, Lee & Muller 1973, Erskian & Lipps 1987, Alve & Murray 1994. In South San Francisco Bay, I found that both total foraminiferal standing crop and the standing crops of individual taxa (and to a lesser extent, total biovolume) exhibit seasonal cycles similar to those of sediment organic matter levels.…”
Section: Foraminiferal Population and Environmental Parametersmentioning
confidence: 78%